Investigation of mechanical and surface properties of additively manufactured AlSi10Mg part produced through direct metal laser sintering. (2022) - Soni, Harsh; Limbasiya, Nandita; Jain, Aryan; Gill, Sukhjeet Singh; Sahlot, Pankaj
Abstract: Additive manufacturing (AM) is a cutting-edge method of producing geometrically complex three-dimensional components. Conventional manufacturing has few limitations to build intricate shapes. AM solves the complexity issue by building components with layer-by-layer deposition method. Besides that, AM has less material wastage and superior structural characteristics. Direct Metal Laser Sintering (DMLS) is a powder bed fusion method to fabricate complex geometries. AlSi10Mg is used in a variety of structural applications due to its high strength, hardness, and dynamic characteristics. In this study, the mechanical and surface properties of additively manufactured AlSi10Mg parts by DMLS method have been investigated and compared with the properties of conventional casting samples. Mechanical and surface characteristics such as density, tensile strength, hardness, and surface roughness have been examined. The energy density of 56 J/mm 3 is applied to melt powder particles by keeping laser power 125 W, layer thickness 30 µm, hatch space 135 µm and scanning speed 550 mm/s. The average density of 96.70 % is obtained for AM manufactured AlSi10Mg samples. The tensile strength of 377 MPa with 5% elongation and Vickers hardness of 102.4 HV has been achieved for AM-built samples. The surface roughness of 6 Ra has been attained for as-built AM AlSi10Mg part. Mechanical properties were observed better in additively manufactured components as compared to conventionally casted aluminium alloy. This research study would help in the selection of process parameters to obtain better mechanical properties for additively manufactured compared to cast AlSi10Mg alloy.